On the determination of J-resistance curve of metallic materials using the unloading compliance technique and normalization method - Leite, A. (2018)
In the present work, a study is made about the experimental determination of the fracture resistance curve (R curve) of metallic materials, using the methods: resistance curve and normalization, guided by the ASTM E 1820 standard. The resistance curve method, used here, consists in obtaining the “R curve” (expressed in integral J) through a single specimen. Within this method, the elastic compliance technique was used to obtain crack extension values. The normalization method consists in obtaining the resistance curve (expressed in integral J) directly from the force vs displacement diagram and the initial and final crack lengths, measured at the fracture surface. wo sets of specimens of two metallic materials were tested. Two specimens from each set were submitted to the normalization method, while the remaining were studied with the resistance curve method, implemented in the Instron Wavematrix software, based on the procedure of ASTM E 1820. It was not possible to obtain the value of Fracture Toughness in plain strain, JIC, since ductile crack sizes did not comply with all mandatory items of the standard ASTM E 1820, namely a crack tunnelling effect was observed, being the crack front much deeper than its value near the free surface Within each material, the respective resistance curves were compared using both methods.